2019
DOI: 10.1177/1477370819859462
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of violence against women in Europe: Assessing individual- and country-level factors

Abstract: This study analyses individual- and country-level factors influencing women’s perceptions of the prevalence of violence against women in their countries. Multilevel modelling was used to study 39,377 women residing in 28 member states of the European Union (EU). Individual-level predictor variables included direct victimisation, vicarious victimisation, avoidant and defensive behaviours, awareness, and sociodemographic characteristics. At the country level, we accounted for an index of gender equality and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…Our results reveal that knowing IPVAW victims is linked to an increased perception of severity. This is consistent with previous research, indicating that individuals acquainted with victims are less tolerant of IPVAW (Gracia et al, 2020; Vives-Cases et al, 2018) and perceive it as a more prevalent issue (Vázquez et al, 2019). Baldry and Pagliaro (2014) have suggested that relationships with victims of IPVAW could heighten awareness of the severe repercussions of such violence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results reveal that knowing IPVAW victims is linked to an increased perception of severity. This is consistent with previous research, indicating that individuals acquainted with victims are less tolerant of IPVAW (Gracia et al, 2020; Vives-Cases et al, 2018) and perceive it as a more prevalent issue (Vázquez et al, 2019). Baldry and Pagliaro (2014) have suggested that relationships with victims of IPVAW could heighten awareness of the severe repercussions of such violence.…”
Section: Discussionsupporting
confidence: 92%
“…Hammock et al (2015) argue that individuals may be more likely to recognize the actual or potential harm of demeaning or controlling behaviors after experiencing them. This hypothesis is consistent with the results of Vázquez et al (2019), which indicated that women in the European Union who had experienced IPVAW and/or knew other victims were more likely to perceive IPVAW as a frequent phenomenon in their countries. Similarly, Vives-Cases et al (2018) found that respondents who did not know any victims of IPVAW showed a higher acceptance of such violence; and Gracia & Herrero, 2006 reported that men who knew victims exhibited lower levels of IPVAW acceptability.…”
Section: Introductionsupporting
confidence: 91%
“…Related to the prevalence of supportive attitudes toward IPVAW, several demographic surveys have included brief scales or individual items measuring IPVAW acceptability ( European Commission, 2010 ; Yount et al, 2011 ; World Health Organization [WHO], 2013 ; European Union Agency for Fundamental Rights [EUAFR], 2014 ; Gracia and Lila, 2015 ; Herrero et al, 2017 ; Schwab-Reese and Renner, 2017 ; Sardinha and Najera, 2018 ; Tausch, 2019 ; Vázquez et al, 2019 ). For instance, the 2010 Eurobarometer ( European Commission, 2010 ) showed that in the European Union, an average of 84% of those surveyed considered that IPVAW was unacceptable and should always be punishable by law (with variations across countries from 93% to 66%) ( Gracia and Lila, 2015 ); 12% of respondents believed that IPVAW was unacceptable but not always punishable by law, also with substantial variation across countries (i.e., from a low of 5% in Greece to a high of 32% in Finland); and only a very small fringe of those interviewed thought that IPVAW was acceptable in certain circumstances (2%) or in all circumstances (1%).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect perceptions and attitudes toward violence against women (Vázquez et al, 2019). Some of these factors include gender, educational status, culture, exposure to or witnessing domestic violence in childhood, employment status, and family structure.…”
Section: Discussionmentioning
confidence: 99%
“…Significant studies have been performed on various platforms to reduce and prevent violence against women worldwide. Globally, violence against women is recognized as a problem; however, multiple programs targeting all segments of the society are needed to reduce and prevent violence against women (Vázquez et al, 2019). In Turkey, the current literature investigating the reasons for violence against women and evaluating the views of both women and men is limited.…”
Section: Introductionmentioning
confidence: 99%